78.9k views
5 votes
Solve for x. In the equation 9x +1/3= x-13

User TonyM
by
5.1k points

2 Answers

0 votes

Answer:

Explanation:

9x+
(1)/(3)=x-13

9x*3+1/3=x-13

27x+1/3=x-13

27x+1=3(x-13)

27x+1=3x-39

27x-3x=-39-1

24x=-40

x=-5/3

x=-5/3

User Loup
by
5.0k points
4 votes

Answer:

x = -
(5)/(3)

Explanation:

Given

9x +
(1)/(3) = x - 13 ( multiply through by 3 to clear the fraction )

27x + 1 = 3x - 39 ( subtract 3x from both sides )

24x + 1 = - 39 ( subtract 1 from both sides )

24x = - 40 ( divide both sides by 24 )

x =
(-40)/(24) = -
(5)/(3)

User Mdh
by
5.2k points